A research on soccer teams` brand associations - Yildiz, Y. (The Sport Journal, 2016)
The identification of brand associations of consumers with respect to sports teams has a crucial role in decisions of sports managers who aim at enhancing the efficiency of their marketing endeavors. The objective of this research is to measure brand associations considering soccer teams and investigate the significance of brand associations attached to soccer teams. Seven-hundred and forty-nine soccer team supporters participated in this research. As a result of the research, it has been found that success, social interaction and brand marks are the most significant brand association dimensions for soccer teams.